THE INFLUENTIAL FACTORS TOWARDS CREDIT UNION MEMBERS (STUDIES IN CU NETWORK BOARDS OF CU IN KALIMANTAN) - Amu Lanu A. Lingu (Journal of Economics, Business, and Accountancy Ventura, 2011)
Credit Unions, in Indonesia, have well-developed and played an important role in supporting its members ‘economic empowerment. In 2008, there were 33 Regional Coordinating Bodies of Credit Cooperation (BK3D) and one Central Office of Credit Cooperation (PUSKOPDIT). Among them, it is Kalimantan Coordinating Body of Credit Union (BKCUK). This research attempts to find out the relationship and influences among the variables as used in this re- search. The data which include the abovementioned key variables were collected from re- spondents using questionnaires. Path analysis was used to estimate the magnitude of direct or indirect causal relationships between exogenous variables and endogenous variables. AMOS Version 16 was used to perform the analysis. Results of the study shows that: (i) lead- ership of managers was directly affected by both strategic plan and financial performance; (ii) quality of product/service was directly affected by strategic plan, and was indirectly af- fected by  financial performance  through  managers’  leadership;  and  (iii) satisfaction of PCU’s members was directly affected by either leadership of managers or quality of prod- uct/service, and was indirectly affected by financial performance and strategic plan through leadership of manager. Results of the study shows, That: (i) the leadership of managers was directly affected by both the strategic plan and financial performance, (ii) quality of product / service was directly affected by the strategic plan, and was indirectly affected by financial performance through managers’ leadership ; and (iii) the satisfaction of PCU’s members was directly affected by Either leadership of managers or quality of product / service, and was indirectly affected by financial performance and strategic plan through leadership of manager.